Antiallergic effect of the atomized extract of rhizome of Curcuma longa, flowers of Cordia lutea and leaves of Annona muricata - Arroyo-Acevedo J; Franco-Quino C; Ruiz-Ramírez E; Chávez-Asmat R; Anampa-Guzmán A; Raéz-González E; Cabanillas-Coral J (Dove Medical Press, 2016)
Jorge Arroyo-Acevedo,1–3 Cesar Franco-Quino,4,5 Eliberto Ruiz-Ramirez,4,5 Roberto Chávez-Asmat,1,6 Andrea Anampa-Guzmán,7,8 Ernesto Raéz-González,3 José Cabanillas-Coral9 1Pharmacology Laboratory, Institute of Clinical Research, National University of San Marcos, Lima, Peru; 2Institute of Clinical Research, National University of San Marcos, Lima, Peru; 3Institute of Pathology, Faculty of Medicine, National University of San Marcos, Lima, Peru; 4Laboratory of Pharmacology and Physiology, Faculty of Dentistry, National University of San Marcos, Lima, Peru; 5Graduate Unit, Faculty of Pharmacy and Biochemistry, National University of San Marcos, Lima, Peru; 6Association for the Development of Student Research in Health Sciences (ADIECS), Lima, Peru; 7School of Human Medicine, Faculty of Medicine, National University of San Marcos, Lima, Peru; 8Sociedad Científica de San Fernando (SCSF), Lima, Peru; 9Faculty of Medicine, National University San Luis Gonzaga of Ica, Ica, Peru Introduction: Allergies are a problem that greatly affects the population, and hence the use of antiallergic medications is fairly widespread. However, these drugs have many adverse effects. The use of medicinal plants could be an option, but they need to be evaluated. Objective: This study was designed to evaluate the antiallergic effect of the atomized extract of rhizome of Curcuma longa, flowers of Cordia lutea, and leaves of Annona muricata. Materials and methods: Twenty-four New Zealand white albino rabbits were randomized into 2 groups. Group A received the atomized extract diluted in physiological saline (APS) and group B received it diluted in Freund’s adjuvant (FA). Then, the back of each rabbit was divided into 4 quadrants. The A-I quadrant received only physiological saline. The A-I quadrants of each rabbit conformed the PS group. The following 3 quadrants received the APS in 10 µg/mL, 100 µg/mL, and 1,000 µg/mL, respectively. The B-I quadrant received only FA. The B-I quadrants of each rabbit conformed the FA group. The following 3 quadrants received the AFA in 10 µg/mL, 100 µg/mL, and 1,000 µg/mL, respectively. The occurrence of erythema and edema was recorded according to the Draize scoring system and the primary irritation index. After 72 hours, biopsies were performed. Results: The AFA group presented significantly less erythema and edema compared to the FA group (P<0.05). The histopathologic evaluation at 72 hours showed normal characteristics in the APS group. Conclusion: Considering the clinical and histopathological signs, we conclude that the administration of the atomized extract of rhizome of C. longa, flowers of C. lutea, and leaves of A. muricata lacks antigenic effect but could have an antiallergenic effect in a model of dermal irritation in rabbits. Keywords: rabbit, irritation, erythema, edema